TNFα PRODUCTION AND APOPTOSIS REGULATION IN VIRAL HEPATITIS TYPE C - V. V. Novitsky; N. V. Rjazantseva; O. B. Zhukova; T. T. Radzivil; E. V. Beloborodova; A. P. Zima; I. O. Naslednikova; M. M. Litvak; S. L. Mikheev (Медицинская иммунология)
Abstract. Chronical course of infection caused by hepatitis C virus is accompanied by increase Fas-positive lymphocytes of peripheral blood. Cultivation of agglutinin-stimulated mononuclear blood cells of patients with chronic hepatitis C revealed inhibition of apoptotic reactions of blood lymphocytes. This fact correlated with decrease in production of TNFα and accelerated synthesis of soluble receptor for this cytokine. We suggest a virus-specific influence on apoptosis regulation of target cells.